The effect of D and L- amino Acids on Biofilm Formation in Different Microorganisms (Iraqi Journal of Science, 2022)
The D-enantiomers of amino acids have been thought to have relatively insignificant function in biological processes like, D-amino acids are sometimes found in proteins that are not synthesized by ribosomes. While L-amino acids clearly permanent in nature, D-amino acids have previously inapprehensible regulatory roles in the bacterial kingdom, any diverse of bacterial phyla made from these D-amino acids regulate cell wall remodeling in stationary phase and cause biofilm dispersal in aging bacterial communities. Clarification the mechanism by which D-amino acids given cell wall reorganization and biofilm disassembly will undoubtedly discover new paradigms for understanding how extra cytoplasmic processes are regulated as well as lead to development of novel therapeutic. Results of this study evaluated that 50 and 100mM of D-glycine have inhibitory effect on Klebsiella pneumonia, and Staphylococcous aeurues biofilm formation. Also50 and 100mM of D-aspartic acid have the same inhibitory effect on Escherichia coli, and Staphylococcous aureus biofilm formation. The mix of 100Mmof both D-glycine and aspartic acid have more effective inhibitory activity on Escherichia coli, and Staphylococous auerues biofilm formation than when it used alone. While the use of L-serine, L-isoleucine and L-tyrosine have no inhibition activity on biofilm formation of Klebsiella pneumonia, Staphylococcous aurues and Escherichia coli.